Atmospheric Pressure Cold Plasma (ACP) Treatment a New Technique to Improve Microstructure and Textural Properties of Healthy Noodles Fortified with Mango Flour - Abidin, Noor Shazliana Aizee; Rukunudin, Ibni H.; Zaaba, Siti K.; W. Omar, Wan A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The effect of atmospheric pressure cold plasma (ACP) on microstructural, textural and sensory properties of healthy noodles fortified with mango flour was studied. Atmospheric pressure cold plasma was carried out using helium gas with a flow rate of 1000 ml/min at room temperature. The electrodes were powered by a direct current (DC) power supply voltage of 16.6 kV wrapped around the quartz glass tube to develop plasma plume. SEM for microstructural observation was done to study the changes in surface morphology of plasma treated noodles. It was observed that after the plasma treatment the gluten and fiber content on the noodles surface more coherent and smoother between gluten network and starch granules than the control with respect to plasma power and time of treatment. Atmospheric pressure cold plasma treatment maintained the hardness, springiness and gumminess of control noodles without mango flour (CNT) and noodles fortified with mango flour (NMFT) significantly (P<0.05) compared to untreated control noodles (CN) and untreated mango flour fortified noodles (NMF). The results suggest that ACP is an effective technique for enhancing the gluten strength and improving the qualities of noodles fortified with mango flour.